2006
DOI: 10.1007/s10681-006-9327-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes in durum wheat yield components and associated traits in Italian and Spanish varieties during the 20th century

Abstract: Twelve field experiments comparing 24 durum wheat varieties from three periods-old (<1945), intermediate and modern (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)-were carried out in order to ascertain the advances made in durum wheat yield components and related traits in Italian and Spanish germplasm. Grain yield improvements were based on linear increases in the number of grains per m 2 and harvest index, while grain weight and biomass remained unchanged. Yield per plant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
132
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 30 publications
26
132
3
2
Order By: Relevance
“…PCR-based markers specific for the base pair responsible for the semi-dwarf phenotype were used to identify specifically wild-type (Rht-B1a) and mutant (Rht-B1b) allelic variants at the Rht-B1 locus following the methodology described by Ellis et al (2002), thus allowing classifying the cultivars into two groups: tall, carrying the RhtB1a allele, and semi-dwarf, with the Rht-B1b allele. This methodology confirmed the presence of the Rht-B1b allele in the genome of the Italian cultivar 'Adamello', which had previously been considered not to carry any dwarfing allele (Isidro et al 2011;Álvaro et al 2008a, 2008b, 2008cRoyo et al 2007), according to the results of the test for sensitivity to gibberellic acid (Gale and Gregory 1977). At anthesis (Zadoks stage 65, Zadoks et al 1974) plant height was measured from the soil to the top of the spike excluding the awns, and the entire plants, including the roots, were removed from the tubes (Fig.…”
Section: Plant Materialssupporting
confidence: 71%
See 2 more Smart Citations
“…PCR-based markers specific for the base pair responsible for the semi-dwarf phenotype were used to identify specifically wild-type (Rht-B1a) and mutant (Rht-B1b) allelic variants at the Rht-B1 locus following the methodology described by Ellis et al (2002), thus allowing classifying the cultivars into two groups: tall, carrying the RhtB1a allele, and semi-dwarf, with the Rht-B1b allele. This methodology confirmed the presence of the Rht-B1b allele in the genome of the Italian cultivar 'Adamello', which had previously been considered not to carry any dwarfing allele (Isidro et al 2011;Álvaro et al 2008a, 2008b, 2008cRoyo et al 2007), according to the results of the test for sensitivity to gibberellic acid (Gale and Gregory 1977). At anthesis (Zadoks stage 65, Zadoks et al 1974) plant height was measured from the soil to the top of the spike excluding the awns, and the entire plants, including the roots, were removed from the tubes (Fig.…”
Section: Plant Materialssupporting
confidence: 71%
“…In addition to the reduced height of the plant, the Rht-B1b allele has well-known pleiotropic effects on plant growth, and morphological and physiological characters (Gale and Youssefian 1985;Li et al 2011;Rebetzke et al 2012). It increases yield, mostly under favourable conditions, by altering the proportion of dry matter allocated to grain (De Vita et al 2007;Royo et al 2007Royo et al , 2008Álvaro et al 2008a). However, the effect of the Rht-B1b allele on the root system has been poorly explored (Waines and Ehdaie 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(B), Table 2). Similarly to Royo et al (2007) conclusions, increases in grain yield were due to changes in photosynthates partitioning within the plant. Guarda et al (2004) and Shearman et al (2005) results showed that number of grains per unit land area contributed to the genetic gain of grain yield.…”
Section: Cereal Research Communications 42 2014supporting
confidence: 54%
“…Past genetic gains in wheat plants have been widely associated with increased harvest index and grain per m 2 and decreasing stem length (Royo et al 2007).…”
mentioning
confidence: 99%